Battle Tested! - McCausland, Jeffrey; Vossler, Tom (Ascent Audio, 2020)
You may never visit the Gettysburg battlefield, but understanding historic lessons from Battle Tested! will have a profound influence on not only your leadership abilities, but also your life, organizations, and career. In order to be a truly effective leader, it is necessary to learn as much as possible from the examples of history-the disasters as well as the triumphs. At Gettysburg, Union and Confederate commanders faced a series of critical leadership challenges under the enormous stress of combat. The fate of the nation hung in the balance. These leaders each responded in different ways, but the concepts and principles they applied during those traumatic three days contain critical lessons for today's leaders that are both useful and applicable-whether those leaders manage operations at a large corporation, supervise a public institution, lead an athletic team, or govern a state or municipality. In the twenty-first century, leadership is the indispensable quantity that separates successful organizations from failures. Successful leaders communicate vision, motivate team members, and inspire trust. One must move both people and the collective organization into the future while, at the same time, dealing with the past. A leader must learn to master the dynamic requirements of decision-making and change.